Analysis of physical disabilities by hanseníase in a city of the interior of Maranhão, Brazil (Research, Society and Development, 2020)
Objective: To analyze the degree of incapacity in leprosy patients assisted between the years of 2012 and 2016. Method: Epidemiological and documentary study, based on cases reported by Sinan de Caxias - MA, from 2012 to 2016. all cases of leprosy reported during the period, totaling 372 patients. For the data analysis, absolute and percentage distributions were obtained. Epi Info software (version 3.7 for Windows) was used. Results: Leprosy mainly affects individuals of brown color, male and with a median age of 50 years. There is a predominance of degree 0 of physical disability, of the dimorphic and virchowian clinical form, indicating the late detection of the disease. Conclusion: The cases with physical disabilities mainly affect patients with positive bacilloscopy and multibacillary clinical forms, considered as the main source of infection of the disease, maintenance of the transmission chain and contributing to the appearance of disabilities.